2016
DOI: 10.2174/1874306401610010001
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Pressure Response During Exercise in COPD: A Correlation with C-Reactive Protein (hsCRP)

Abstract: Background: The non-invasive assessment of pulmonary haemodynamics during exercise provides complementary data for the evaluation of exercise tolerance in patients with COPD. Methods: Exercise echocardiography in the semi-supine position was performed in 27 patients with COPD (C) with a forced expiratory volume in one second (FEV1) of 36±12% predicted and 13 age and gender-matched non-COPD subjects (NC). COPD patients also underwent cardiopulmonary exercise testing with gas exchange detection (CPET). Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
(43 reference statements)
2
15
0
4
Order By: Relevance
“…Összességében az aerob testmozgás bármilyen intenzitáson jótékony hatással van a metabolikus szindróma összes komponensére túlsúlyos vagy elhízott betegek esetén [26][27][28][29].…”
Section: Megbeszélésunclassified
“…Összességében az aerob testmozgás bármilyen intenzitáson jótékony hatással van a metabolikus szindróma összes komponensére túlsúlyos vagy elhízott betegek esetén [26][27][28][29].…”
Section: Megbeszélésunclassified
“…LTx is a potential treatment of end-stage severe pulmonary diseases such as COPD, ILD, Bronchiectasis, CF and PAH. We have to choose individual, closely controlled and supervised training programs for our patients, based on the different comorbidities and side effects of the advanced chronic respiratory diseases (PAH, dynamic hyperinflation) and permanent chronic inflammation (35)(36)(37)(38)(39)(40). Nutritional and functional status are impaired, and low physical activity levels can be detected in advanced pulmonary diseases (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic in ammation itself is associated with decreased serum HDL and increased TG levels in COPD [23], it has been shown that in ammatory cytokines disrupt lipid metabolism, there is an inverse correlation between serum HDL and IL-6 levels [24]. Patients with COPD are physically inactive, which further increases the risk of dyslipidemia, and they often use corticosteroids, which also increases the occurance of dyslipidemia and obesity [25].…”
Section: Discussionmentioning
confidence: 99%